Some factors which may affect the attainment of implicit and explicit knowledge in learning English as a second or foreign language - Mariana Gotseva (English Studies at NBU, 2015)
This article is an attempt to shed some more light on certain factors, related to individual differences in the process of second/foreign language acquisition/learning, proven by previous research in the field of second language acquisition (SLA). These are factors which may affect the final attainment of adult learners' implicit and explicit knowledge of English as a second/foreign language and their proficiency. A study based on empirical data collected from a sample of 103 participants, through a battery of tests, aimed at tapping into the attainment of implicit or explicit knowledge of ESL/EFL, was conducted to explore certain factors such as: starting age of learning; length of exposure to English as a second/foreign language in a target language country; length of learning and type of input received, which have a statistically significant impact on attainment and on ESL/EFL proficiency. The results were analysed using SPSS software.